INTENSIVE PRACTICE AND LANGUAGE LABS - Safarova Dildora; Ruzmanova Muxlisa; Abdullaxo’jayeva Feruzabonu; Usmonova Nilufar (TADQIQOTLAR, 2025)
This article explores the crucial role of intensive practice and language laboratories in developing language skills. With the advancement of technology, language labs have become an essential tool in foreign language instruction, offering immersive, interactive, and self-paced learning environments. Intensive practice, combined with audio-visual materials, fosters listening, speaking, and comprehension. The article also emphasizes the integration of language labs in educational settings to enhance learners’ fluency, motivation, and autonomy. It is particularly useful for language teachers, curriculum developers, and policymakers aiming to implement modern strategies in language education.